Social work in mental health : areas of practice, challenges and way forward - Francis, Abraham P. (New Delhi : Sage, 2014)
"Social Work in Mental Health brings together a range of scholarly reflections and writings on the different roles of a social worker in the field of mental health. It provides a holistic picture to introduce readers to the wider issues of social work and mental health practice. The book offers a detailed discussion on the theoretical and practice frameworks that are based on social justice and human rights perspectives. It not only provides an overview of intervention strategies but also directs readers$1 (Battention to an alternative way of addressing mental health issues. The author presents a cross-cultural and global perspective of mental health, but with specific references to India and Asia. He also addresses some of the recent debates in recovery, partnerships and strengths-based practices. The book has been specially designed for social work students, human service professionals and mental health practitioners and academicians. Areas of Practice, Challenges and Way Forward offers the readers an exposure to the many different contexts within which social workers come into contact with those experiencing mental health concerns. The specific needs for particular community groups, including children, young and older people, are identified."--s
Keywords: Psychiatric social work